2011
DOI: 10.1002/qj.879
|View full text |Cite
|
Sign up to set email alerts
|

The orographic impact on patterns of embedded convection during the August 2005 Alpine flood

Abstract: Convective precipitation structures during an Alpine heavy precipitation event inAugust 2005 are investigated utilising a mesoscale non-hydrostatic numerical model and observational data. The focus is on the mechanisms of convective initiation during the very beginning of the event, when organised cellular updraughts enhanced the precipitation over the southern German Alpine foreland. A set of sensitivity experiments with systematically modified topography is conducted in order to investigate the role of singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
1
17
0
1
Order By: Relevance
“…The long axis of storms is usually parallel to the direction of wind on the leeside. Langhans et al (2011) revealed that the intensity of one of the rainbands they studied was related to the location of the topography.…”
Section: Introductionmentioning
confidence: 95%
“…The long axis of storms is usually parallel to the direction of wind on the leeside. Langhans et al (2011) revealed that the intensity of one of the rainbands they studied was related to the location of the topography.…”
Section: Introductionmentioning
confidence: 95%
“…Also, sensible heat fluxes in mountainous regions induce slope and valley breezes which transport heat and moisture both vertically and horizontally (Whiteman, ), modulating CIN and affecting low‐level shear. Langhans et al () demonstrated that squall lines can be weakened or suppressed by increased CIN due to descending flow in the lee of a ridge.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a microphysical process and a triggering of cloud convection are explicitly calculated in experiments using a fine mesh size (e.g., Prein et al 2015), resulting in an improvement in the thermodynamical processes associated with cumulus convection. A finer mesh size also improves the computation of orographic precipitation because it can resolve the dynamical effect of mountains on heavy precipitation (Leung and Qian 2003;Langhans et al 2011). For these reasons, improved performance is expected from numerical models in experiments using a higher spatial resolution without the CP, relative to experiments using a coarse mesh size but with the CP.…”
Section: Introductionmentioning
confidence: 99%